Analysis of Decision Number 23/Pid.Sus-Anak/2024/Pn Smn Concerning the Sentencing of a Child Perpetrator of a Narcotics Crime Based on Restorative Justice - Vynky, Vynky; Mubarrak, Muhammad Zaki (LEGAL BRIEF, 2025)
This study aims to analyze the judicial reasoning behind the sentencing of a juvenile involved in a narcotics offense and evaluate the application of restorative justice principles in Decision Number 23/Pid.Sus-Anak/2024/PN.Smn at the Sleman District Court. Utilizing a normative juridical research design with statutory and case approaches, the research relies on the analysis of legal documents, statutory provisions, and court decisions. The findings indicate that the judge's considerations encompassed both juridical factors, such as the fulfillment of evidentiary standards and legal provisions, and non-juridical aspects, including the child’s age, behavior, and social background. Despite the presence of mitigating circumstances and the legal eligibility for diversion, the restorative justice mechanism was not applied. This reflects a prevailing punitive orientation in narcotics-related juvenile cases, revealing a disjunction between the protective framework under the Juvenile Justice Law and the stringent enforcement of the Narcotics Law. The study concludes that there is an urgent need for greater integration of restorative justice principles in juvenile drug cases to ensure rehabilitative outcomes and uphold the best interests of the child